2014
DOI: 10.1039/c4cp00219a
|View full text |Cite
|
Sign up to set email alerts
|

Analytical tools for single-molecule fluorescence imaging in cellulo

Abstract: Recent technological advances in cutting-edge ultrasensitive fluorescence microscopy have allowed single-molecule imaging experiments in living cells across all three domains of life to become commonplace. Single-molecule live-cell data is typically obtained in a low signal-to-noise ratio (SNR) regime sometimes only marginally in excess of 1, in which a combination of detector shot noise, suboptimal probe photophysics, native cell autofluorescence and intrinsically underlying stochasticity of molecules result … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 65 publications
2
48
0
Order By: Relevance
“…Fluorescent proteins probes are more challenging due to poorer photophysical properties, though Moerner reported axial precisions of ~40 nm using yellow fluorescent protein by employing a double helix PSF method with 30 ms per frame sampling [32]. However, since GFP emits approximately an order of magnitude fewer photons on average than YFP prior to photobleaching, and our method involves much faster sampling, also by close to an order of magnitude compared to Moerner's YFP study, our reported axial precision is close to expectation based on the effective signal-to-noise ratio [33]. Our calibration using single GFP molecules also in many ways represents a worst case for axial resolution as many of the transcription factors we image are clustered [7].…”
Section: Calibration and Performance Of The Microscopesupporting
confidence: 69%
“…Fluorescent proteins probes are more challenging due to poorer photophysical properties, though Moerner reported axial precisions of ~40 nm using yellow fluorescent protein by employing a double helix PSF method with 30 ms per frame sampling [32]. However, since GFP emits approximately an order of magnitude fewer photons on average than YFP prior to photobleaching, and our method involves much faster sampling, also by close to an order of magnitude compared to Moerner's YFP study, our reported axial precision is close to expectation based on the effective signal-to-noise ratio [33]. Our calibration using single GFP molecules also in many ways represents a worst case for axial resolution as many of the transcription factors we image are clustered [7].…”
Section: Calibration and Performance Of The Microscopesupporting
confidence: 69%
“…The probability distribution of mS* stoichiometry values in live cells in the absence of mF is shown in Fig. 3 C , rendered using a kernel density estimation that generates an objective distribution that does not depend on the size and location of subjective histogram bins (54). We measured a broad range of stoichiometry values, spanning a range from only a few mS* molecules per focus to several 10s of molecules, with a mean of ∼30 molecules per focus.…”
Section: Resultsmentioning
confidence: 99%
“…In brief, candidate bright fluorescent foci were identified in images using morphological transformation and thresholding. The sub-pixel centroids of these foci were determined using iterative Gaussian masking and their intensity quantified as the summed intensity inside a 5-pixel radius region of interest (ROI) corrected for the mean background intensity inside a surrounding 17 x 17 pixel ROI (Delalez et al, 2010;Leake, 2014). Foci were accepted and tracked through time if they had a signal-to-noise ratio, defined as the mean intensity in the circular ROI divided by the standard deviation in the outer ROI, over 0.4.…”
Section: Slimfield Microscopy and Data Analysismentioning
confidence: 99%